Cerebellar border zone infarcts are often associated with presumed cardiac sources of ischaemic stroke. Issue 1 (July 1995) - Mounier-Vehier, F; Degaey, I; Leclerc, X; Leys, D
Abstract : It has been suggested that most border zone cerebellar infarcts are embolic infarcts or infarcts due to hypercoagulatble states. The aim of this study was to test this hypothesis. Risk factors for the presumed mechanism of stroke (TOAST criteria) were studied in 14 consecutive patients (nine men, five women; age range 29-84 years) with a total of 17 border zone cerebellar infarcts. The presumed cause of stroke was "cardioembolism" in nine patients. Three patients had a dissection of the vertebral artery. Two patients had a negative diagnostic investigation, and one had a cardiac arrest. These findings support the hypothesis that cardioembolism is a frequent mechanism of border zone cerebellar infarcts.